The basic chemistry of exercise-induced DNA oxidation: oxidative damage, redox signaling, and their interplay - Cobley, James N.; Margaritelis, Nikos V.; Morton, James P.; Close, Graeme L.; Nikolaidis, Michalis G.; Malone, John K. (Frontiers in Physiology, 2015)
Acute exercise increases reactive oxygen and nitrogen species generation. This phenomenon is associated with two major outcomes: (1) redox signalling and (2) macromolecule damage. Mechanistic knowledge of how exercise-induced redox signalling and macromolecule damage are interlinked is limited. This review focuses on the interplay between exercise-induced redox signalling and DNA damage, using hydroxyl radical (·OH) and hydrogen peroxide (H2O2) as exemplars. It is postulated that the biological fate of H2O2 links the two processes and thus represents a bifurcation point between redox signalling and damage. Indeed, H2O2 can participate in two electron signalling reactions but its diffusion and chemical properties permit DNA oxidation following reaction with transition metals and ·OH generation. It is also considered that the sensing of DNA oxidation by repair proteins constitutes a non-canonical redox signalling mechanism. Further layers of interaction are provided by the redox regulation of DNA repair proteins and their capacity to modulate intracellular H2O2 levels. Overall, exercise-induced redox signalling and DNA damage may be interlinked to a greater extent than was previously thought but this requires further investigation.